Study of Complete Genome Sequences of Rotavirus A Epidemics and Evolution in Japan in 2012–2014 - Fujii, Yoshiki; Doan, Yen Hai; Suzuki, Yoshiyuki; Nakagomi, Toyoko; Nakagomi, Osamu; Katayama, Kazuhiko (Frontiers in Microbiology, 2019)
A comprehensive molecular epidemiological study using next generation sequencing technology was conducted on 333 rotavirus-positive specimens collected from six sentinel hospitals across Japan over three consecutive seasons (2012–2014). Most of rotaviruses were grouped into five genotype constellations: Wa-like G1P[8], DS-1-like G1P[8], G2P[4], G3P[8] and G9P[8]. Phylogenetic analysis showed that the distribution of strains varied by geographical locations and epidemic seasons. The VP7 genes of different G types were estimated to evolve at 7.26×10^-4 – 1.04×10^-3 nucleotide substitutions per site per year. The Bayesian time-scaled tree of VP7 showed that the time to the most recent common ancestor of epidemic strains within a region was 1–3 years, whereas that of the epidemic strains across the country was 2–6 years. This study provided, for the first time, the timeframe during which an epidemic strain spread locally and within the country and baseline information needed to predict how rapidly rotaviruses spread.